Equipping providers to offer novel MPTs: Developing counseling messages for the Dual Prevention Pill in clinical studies and beyond - Segal, Kate; Harris, Danielle M.; Carmone, Andy; Haddad, Lisa B.; Hadigal, Sanjay; Hatzold, Karin; Jones, Chris; Lathrop, Eva; Mason, Jennifer; Mikulich, Meridith (Frontiers in Reproductive Health, 2023)
Introduction: The Dual Prevention Pill (DPP) is a daily pill co-formulating oral pre-exposure prophylaxis (PrEP) and combined oral contraception (COC). Clinical cross-over acceptability studies for the DPP require training providers to counsel on a combined product. From February 2021-April 2022, a working group of eight HIV and FP experts developed counseling recommendations for the DPP based on existing PrEP/COC guidance. Assessment of policy/guidelines options and implications: The working group conducted a mapping of counseling messages from COC and oral PrEP guidance and provider training materials. Six topics were prioritized: uptake and counseling recommendations for the DPP were developed. Missed pills was the topic with the most complexity, raising questions about whether women could “double up” on missed pills or skip the last week of the pack to recover protection faster. Uptake required aligning the time to reach protective levels for both DPP components and explaining the need to take DPP pills during week 4 of the pack. The potential intensity of DPP side effects, given the combination of oral PrEP with COC, was an important consideration. Discontinuation and switching looked at managing risk of HIV and unintended pregnancy when stopping or switching from the DPP. Guidance on drug interactions contended with differing contraindications for COC and PrEP. Monitoring required balancing clinical requirements with potential user burden. Actionable Recommendations: The working group developed counseling recommendations for the DPP on the six prioritized topics (uptake, missed pills, side effects, discontinuation and switching, drug interactions, monitoring), to be tested in clinical acceptability studies. Discussion: Developing recommendations for the DPP as a novel MPT posed unique challenges, with implications for efficacy, cost, and user and provider comprehension and burden. Incorporating counseling recommendations into clinical cross-over acceptability studies allows for real-time feedback from providers and users. Supporting women with information to use the DPP correctly and confidently is critically important for eventual scale and commercialization.